Pediatric Smoflipid Therapy: Patient Response and Safety Concerns. Issue 4 (22nd June 2020) - Huff, Katie A.; Breckler, Francine; Cruse, Wendy; Szeszycki, Elaina; Vanderpool, Charles
Abstract: Background: Intestinal failure–associated liver disease (IFALD) occurs in ≤85% of neonates receiving prolonged parenteral nutrition. Strategies for treatment of IFALD include alternative lipid therapies, such as Smoflipid (Fresenius Kabi). In this study, we reviewed our institutional Smoflipid use, including predictors of patient response and safety concerns. Methods: This is a retrospective chart review of all pediatric patients who received Smoflipid therapy over a 2‐year period at Riley Hospital for Children. Forty‐two patients (89%) had cholestasis at the start of Smoflipid therapy and were included in group analysis. We compared patients based on response to Smoflipid therapy, identifying associations and predictors of patient response. We also documented patient safety concerns, including essential fatty acid deficiency (EFAD), rapid infusion, and compatibility/access issues. Results: Sixteen patients (38%) with cholestasis had resolution with Smoflipid. Those patients with resolution were older at initiation (58 vs 33.5 days; P = .010), treated with Smoflipid for longer (85.5 vs 41 days; P = .001), and had lower direct bilirubin at the start of Smoflipid therapy (3.7 vs 5.2 mg/dL; P = .035). We identified multiple safety concerns, including EFAD (54%), rapid infusion (17%), and missed doses (51%). No patient characteristics were found to correlate with Smofllpid therapy and diagnosis of EFAD. Conclusion: In our patient population, Smoflipid therapy led to cholestasis resolution in patients with lower direct bilirubin or less‐severe IFALD. Use of Smoflipid is also associated with significant safety concerns, and its use should be coupled with close monitoring in pediatric patients, particularly in neonates.